Review: Indole Alkaloids and Antimalarial Activity in the Tabernaemontana Species - Hutami, Anisa Tri; Ekasari, Wiwied; Rudyanto, Marcellino (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Malaria, caused by Plasmodium parasites, is a highly prevalent and lethal illness that shows persistent ability to develop resistance. Antiplasmodial compounds that are indole-based prevent hemozoin formation, exhibiting efficacy against chloroquine-resistant Plasmodium strains. Tabernaemontana is a member of the genus comprised  to the Apocynaceae family and has long been known for its efficacy in traditional and herbal tribal medicine. Apocynaceae can be recognized by the existence of indole alkaloids, and Tabernaemontana spp. is widely identifiable for its ability to synthetize a wide variety of indole alkaloids. Objective: This literature review seeks to provide a comprehensive summary of indole alkaloid compounds from Tabernaemontana spp. and the effectiveness of Tabernaemontana spp. as antimalarials. Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocols were followed to explore the PubMed, Sage Journal, ScienceDirect, and Wiley Library databases. Results: 23 publications on the antimalarial activity and indole alkaloids of several species of the genus Tabernaemontana were discovered. Conclusion: Various species of Tabernaemontana contain indole alkaloids, and extracts of the plant or parts of the plant and isolates have weak to strong antimalarial activity.